A Research Manual: for writing right - Avwokeni, Arthur J. (Lagos, Nigeria University of Lagos Press, 2022)
This book illustrates the English language in the context of research reporting, with emphasis o American English. It adopts a tete-a-tete manner of enquiry to maintain the tempo.
Includes bibliography, index
osc 14/02/2024
Loans
Keywords: Research - Manual